METHODOLOGY FOR STUDY AND ANALYSIS OF EVALUATION CRITERIA - Amanov, Alisher (Журнал иностранных языков и лингвистики, 2023)
In our article, teachers and testers look at the criteria used in language assessment. They should familiarize themselves with the so-called rating scales for language assessment. Although it is difficult to discuss them in detail, some basic information should be mentioned as they are very important for those who are clueless like Uzbek students and even teachers. The following language scales are taken into account: